Epidermal graft encourages wound healing by down‐regulation of gap junctional protein and activation of wound bed without graft integration as opposed to split‐thickness skin graft. Issue 3 (9th March 2021) - Kanapathy, Muholan; Hachach‐Haram, Nadine; Bystrzonowski, Nicola; Becker, David L.; Mosahebi, Afshin; Richards, Toby
Abstract: Wound coverage by split‐thickness skin graft (SSG) and epidermal graft (EG) shortens healing time, with comparable outcomes. However, the healing mechanism of EG is not as well understood as SSG. The difference in the healing mechanisms of EG and SSG was investigated using gap junctional proteins, proliferative marker, and cytokeratin markers. Paired punch biopsies were taken from the wound edge and wound bed from patients undergoing EG and SSG at weeks 0 and 1 to investigate wound edge keratinocyte migratory activities (connexins 43, 30, and 26), wound bed activation (Ki67), and the presence of graft integration to the wound bed (cytokeratins 14 and 6). Twenty‐four paired biopsies were taken at weeks 0 and 1 (EG, n = 12; SSG, n = 12). Wound edge biopsies demonstrated down‐regulation of connexins 43 ( P = .023) and 30 ( P = .027) after EG, indicating accelerated healing from the wound edge. At week 1, increased expression of Ki67 ( P < .05) was seen after EG, indicating activation of cells within the wound bed. Keratinocytes expressing cytokeratins 6 and 14 were observed on all wounds treated with SSG but were absent at week 1 after EG, indicating the absence of graft integration following EG. Despite EG and SSG both being autologous skin grafts, they demonstrate different mechanisms of wound healing. EG accelerates wound healing from the wound edges and activates the wound bed despite not integrating into the wound bed at week 1 post‐grafting as opposed to SSG, hence demonstrating properties comparable with a bioactive dressing instead of a skin substitute.